Influence of SNP*SNP interaction on BMI in European American adolescents: findings from the National Longitudinal Study of Adolescent Health. Issue 2 (20th April 2015) - Young, K. L.; Graff, M.; North, K. E.; Richardson, A. S.; Bradfield, J. P.; Grant, S. F. A.; Lange, L. A.; Lange, E. M.; Harris, K. M.; Gordon‐Larsen, P.
Summary: Background: Adolescent obesity is predictive of future weight gain, obesity and adult onset severe obesity (body mass index [BMI] ≥40 kg m −2 ). Despite successful efforts to identify Single Nucleotide Polymorphisms (SNPs) influencing BMI, <5% of the 40–80% heritability of the phenotype has been explained. Identification of gene–gene (G‐G) interactions between known variants can help explain this hidden heritability as well as identify potential biological mechanisms affecting weight gain during this critical developmental period. Objective: We have recently shown distinct genetic effects on BMI across the life course, and thus it is important to examine the evidence for epistasis in adolescence. Methods: In adolescent participants of European descent from wave II of the National Longitudinal Study of Adolescent Health (Add Health, n  = 5072, ages 12–21, 52.5% female), we tested 34 established BMI‐related SNPs for G‐G interaction effects on BMI  z ‐score. We used mixed‐effects regression, assuming multiplicative interaction models adjusting for age, sex and geographic region, with random effects for family and school. Results: For 28 G‐G interactions that were nominally significant ( P  < 0.05), we attempted to replicate our results in an adolescent sample from the Childhood European American Cohort from Philadelphia. In the replication study, one interaction ( PRKD1‐FTO ) was significant after correction for multiple testing. Conclusions: Our results are suggestive of epistatic effects on BMI during adolescence and point to potentially interactive effects between genes in biological pathways important in obesity.